‘John Smith, his Catalogue Raisonné of the Works of the Most Eminent Dutch, Flemish, and French Painters (1829–1842) and the “stigma of PICTURE DEALER”’ - Antoinette Friedenthal (Journal of Art Historiography, 2013)
The monumental nine-volume Catalogue Raisonné by the London art dealer John Smith (1781-1855), covering the works of 41 painters, appeared between 1829 and 1842. In spite of the common recognition of its importance by the specialized secondary literature, this publication has hardly been looked at in a wider art historical context. Reasons for this may be found in the critical reactions by a few contemporary connoisseurs, as well as in the ambivalent status of the genre of the catalogue raisonné. The issues raised by Smith’s volumes and their reception not only pertain to questions of content, they also relate to such fundamental themes as scientific credibility, professional ethos, and the recognition of authority. As far as can be ascertained, this is the first time that criticism of the market’s involvement in this genre makes itself heard. In the 19th century, art history’s search for a viable position among other fields of study led to considerable tensions. These not only resulted in precise demarcations of the discipline’s scope in relation to other academic fields, they also shaped certain patterns of argument which characterize the reception of catalogues raisonnés even today. In addition to addressing these points, the present study also throws some light on the market’s contribution to the formation of categories and systems of classification in the history of art.